Pharmacology of vasoactive drugs - Muri, Estela Maris Freitas; Sposito, Maria Matilde de Mello; Metsavaht, Leonardo (Acta Fisiátrica, 2010)
Peripheral vascular diseases (PVDS) are characterized as a circulation problem in the veins, arteries, and lymphatic system. The main therapy consists of changes in lifestyle such as diet and physical activity. The pharmacological therapy includes the use of vasoactive drugs, which are used in arteriopathies and venolymphatic disorders. The goal of this study was to research the scientific literature on the use and pharmacology of vasoactive drugs, emphasizing the efficacy of their local actions and administration.